Bowel management program for pediatric postoperative fecal incontinence in China: A surgeon's experience. Issue 22 (June 2017) - Wang, Yong; Liang, Huiying; Wu, Qiang; Zheng, Haiqing; Liu, Guangjian; Wen, Zhe; Lan, Menglong; Yu, Jiakang; Zhu, Deli; Liang, Jiankun; Zhang, Jingqi; Xu, Xiaogang; et al.
Abstract : Abstract: The purpose of this article is to report the status of the efficacy of and long-term adherence to the Bowel Management Program (BMP) for fecal incontinence (FI) postoperation in China. Children over 3 years of age with FI postoperation referred to our medical center were included in the study. Evaluations were performed before and 2 years after their clinic visit. The cost of bowel care, improvement in incontinence, health-related quality of life, and family functioning with the BMP were analyzed. A total of 48 children with FI were included in our study, of whom 38 were boys. The median treatment fee was 660.1 dollars. The complications included abdominal pain (4 patients, 8%), occasional vomiting (2 patients, 4%), and hypoglycemia (1 patient, 2%). The incontinence status and health-related quality of life improved significantly after the BMP. Despite the good outcome of the BMP, half of the patients discontinued the program. The BMP is an effective approach to manage FI and improve the patients' quality of life. Poor long-term adherence is currently the main challenge affecting the BMP application in China.